Siberian high pressure and the phenomenon of thermal anomalies resulting from its expansion over Syria Case Study Form (Siberian High pressure,10-15 January,2008) (Journal of Hama University, 2022)
This research aims to study and analyze the  phenomenon of the Siberian high pressure, and the concurrent thermal anomaly with it, and analyze its impact on the surface variables in Syria. In the Syrian weather, changes in the intensity of Siberian high pressure were analyzed in the winter months during the period approved for the study and their impact on the climatic elements during its expansion. At a confidence level of 95% based on the T-test, the effect of thermal anomalies simultaneous with the Siberian high pressure that expanded over Syria during the period (10-15 January 2008) on agricultural production in Lattakia regions was analyzed.